Isotretinoin-induced gynecomastia. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2020)
There are 4 cases of isotretinoin-induced gynecomastia in the literature. Isotreinoin is able, albeit rarely, to cause persistent sexual dysfunction such as finasteride and serotonin reuptake inhibiting antidepressants. While for the latter and for finasteride sexual dysfunction is a known side effect, for isotretinoin it is not even mentioned in the drug’s data sheet. However, according to some Authors (1) who have studied 300 cases of sexual dysfunction, isotretinoin alone is responsible for sexual dysfunction in a number of cases equal to the sum of cases caused by fluoxetine and finasteride. It is likely that the mechanism of action of isotretinoin consists of an androgenic inhibition. Clinically, the action of androgens in acne is known and there are studies showing that isotretinoin decreases testosterone levels (2).